MORTGAGE LENDING IN THE AGRICULTURAL ECONOMY: OPPORTUNITIES AND RISKS - Ruslana Sodoma; Oksana Agres; Olha Havryliuk; Kateryna Melnyk (Фінансово-кредитна діяльність: проблеми теорії та практики)
The development of the agrosphere is possible through the development of all areas of the mortgage (mortgages of agricultural land). However, the efficiency of mortgage lending in agriculture is low. A powerful source of attraction of funds to agricultural production is bank mortgage lending. A prerequisite for its effective development, besides accessibility and transparency for borrowers, is the development of effective instruments for risk management of creditors in the pledging of agricultural land.